Deciphering architectural knowledge as reflective practice: revealing map. Issue 4 (3rd July 2020) - Uzunkaya, Aslı; Paker Kahvecioğlu, Nurbin
ABSTRACT: This study attempts to reveal how reflective knowledge shapes architectural design. With the premise that design embodies personal knowledge, it proposes an alternative way to decipher this subjective medium. It is predicated on the idea that architects have lifelong reflections along with in or on a specific action. With an aim to draw attention to this, a revealing map for reflective practice as research based on architects' journals is proposed. The study progresses through the instrument of two core adaptations from literature. Reinterpreting Christopher Frayling's views on design research and the effort to move Bryan Lawson's thoughts on reflection one step further are the pillars of the study. The themes on reflection which are determined in the adaptation phases are traced in the journals of a participant who is both active in practice and academia; and discussed through a map by focusing on their relations. Combining and simultaneously searching practice and research presented the possibility to study reflective processes of architectural design without being its very subject; and to research practice with ability to enlarge or narrow according to time and person. The study contributes to architectural research by shifting the perspective on reflective knowledge that shapes design processes.